Design optimization of CsPbBr3 nanocrystals into zeolite Beta composites as ultra-stable green emitters for backlight display applications. Issue 36 (10th August 2021) - Li, Bohan; Zhang, Yuchi; Xu, Yan; Xia, Zhiguo
Abstract : CsPbBr3 nanocrystals were encapsulated into zeolite Beta via a high temperature solid-state method demonstrating enhanced luminescent stability. Abstract : CsPbBr3 nanocrystals (NCs) with highly efficient narrow-band green emission are promising candidates in display applications. However, the poor stability of CsPbBr3 NCs is always a challenge for future development. Herein, we designed and prepared CsPbBr3 NCs encapsulated into zeolite Beta (denoted as CsPbBr3 -Beta) composite via an optimized high temperature solid-state method, and the as-obtained power materials exhibited green emission peaking at 520 nm with a narrow full-width at half-maximum (FWHM) of 25 nm and a high photoluminescence quantum yield (∼61%). We further demonstrated the ultra-high luminescent stability of CsPbBr3 -Beta composite by treating under a 150 °C treatment, soaking in water over 30 days, as well as applying in 450 nm light-emitting devices (LED) for 20 days. Ultimately, white-light-emitting devices (WLEDs) constructed by the green-emitting CsPbBr3 -Beta composite and commercial blue chip and red K2 SiF6 :Mn 4+ phosphor achieved a color gamut of 123.5% National Television System Committee standard (NTSC) and high luminous efficiency (LE = 95 lm W −1 ). This work highlights the encapsulation process and feasible solid-state reaction methodology to fabricate CsPbBr3 NCs confined in a microporous molecular sieve with high luminescent stability and performance, significantly expanding its great potential to be used in optoelectronic fields.